Prevalence and genomic diversity of feline leukemia virus in privately owned and shelter cats in Aburrá Valley, Colombia (2020)
The feline leukemia virus (FeLV) belongs to the family Retroviridae; it is the first feline retrovirus discovered and one of the agents that has a great impact on cats’ health and the ecology of the feline population worldwide.